(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
A mathematical model (algorithm) and a nomogram for determination of the compression ratio in flat-pressed composites on the basis of urea-formaldehyde resin as a binding agent and addition of paraffin have been presented in the investigation. By means of an algorithm (KD), the compression ratio of the wood mat during its piezothermal treatment is taken into account. As input data, following parameters are included in the algorithm for KD: bulk densities of the input wood raw material and the composite board; the specific weights of the paraffin and the binding agent; the moisture content of the composite board; the percentage of resin and paraffin; the volumetric swelling of wood.